(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
Studies were carried out on the characterization and glyceride compositions of safflower (Carthamus tinctorius) seed oil. It was observed that safflower seed grown under the soil and climatic condition of Bangladesh contains 32 % of golden yellow coloured oil. The physicochemical characteristics of the oil were studied by the conventional methods and the fatty acid composition by GLC. From the results it is revealed that the oil can be used suitably in paint, varnishes and soap manufacturing industries on account of its high linoleic acid content (75 %), iodine value (148) and saponification value (190). The oil was fractionated into mono-, di-, and triglycerides by silicic acid column choromatography. The trglycerides were accounted for over 90 % of total weight of the oil. Fraction of lipids into three major lipid groups, neutral lipids, glycolipids and phospholipids was carried out by silicic acids column chromatography. The neutral lipids were averaged to 94 % of the total weight of the lipid applied. The percentage composition of individual fatty acids were found to be linoleic acid (75.0), oleic (12.6), palmitic acid (8.4), stearic acid (2.6) and myristic acid (1.4). Bangladesh J. Sci. Ind. Res. 41(3-4), 235-238, 2006